Comparative Analysis Between Chinese Words “突然”、“忽然”and Indonesian Words “Tiba-tiba”, “Mendadak”: 汉语词语“突然”，“忽然”与印尼语词语“Tiba-tiba” ,“Mendadak”对比分析 - Sally Aprianti Tania; Stephen Aji Wardana (Published by Confucius Institute UNS, 2023)
Parasynonym is one of the main challenges in second language acquisition process. Chinese and Indonesian language also had many words which has similar meaning. In this paper, we focused on the comparative analysis between Indonesian words